Fe(III)‐Porphyrin Sonotheranostics: A Green Triple‐Regulated ROS Generation Nanoplatform for Enhanced Cancer Imaging and Therapy. (8th July 2019) - Zhu, Jing; Chu, Chengchao; Li, Dongsheng; Pang, Xin; Zheng, Huili; Wang, Junqing; Shi, Yesi; Zhang, Yang; Cheng, Yi; Ren, En; Cheng, Jingliang; Chen, Xiaoyuan; et al.
Abstract: To address the urgent need for effective sonodynamic therapy (SDT), a facile and efficient strategy is developed for fabricating a new class of sonotheranostics. Herein, a Fe(III)‐porphyrin nano‐sonosensitizer is prepared by a one‐step coordination synthesis, and then anchored with Bis(DPA‐Zn)‐RGD and manganese superoxide dismutase (SOD2) siRNA. Benefiting from the delicate interactions of the Fe(III)‐coordinated nanoformulations, a highly potent sono/gene combinational therapy guided by fluorescence/magnetic resonance imaging is achieved. Importantly, this sonotheranostics significantly enhances the SDT effect of porphyrin through the cancer‐targeted delivery capability and enhanced reactive oxygen species production via triple‐regulated approaches, including down‐regulation of SOD2, depletion of glutathione, and generation of Fenton reaction. This work opens up new perspectives for developing versatile sonotheranostics to overcome the clinical challenges of SDT. Abstract : Novel Fe(III)‐porphyrin sonotheranostics for a fluorescence/magnetic resonance imaging‐guided sonodynamic therapy (SDT) strategy is developed by a facile coordination‐driven self‐assembly procedure. The sonotheranostics could enhance the SDT effect through both the cancer‐targeted delivery capability and enhanced reactive oxygen species production. This novel treatment pattern may act as a promising paradigm to bridge fundamental SDT research with clinical applications.